THE MODE 2 SCIENCE OF LOGIC? - Tiaglo, O. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2017)
Current status of logic and problems of its delivering in Russian and Ukrainian universities are studied in terms of the Gibbons – Nowotny approach. It is concluded that both the status and delivering process are relevant to the Mode 1 basic characteristics. Par excellence they are still oriented to the ideal of completed and universal system of norms of thinking which permits "process of application" only, i. e. external imposition to as if indifferent life or scientific cognition. But this Mode 1 logic as well as maternal Mode 1 society exhausted basic potential already. This fact is confirmed by degradation of its educational condition, and joining of the national educational systems to the Bologna process and a row of other factors support this failing only. Prospects of further advancement and renewal of high status of logic are connected with adaptation to the Mode 2 conditions which presupposes, inter alia, some "sensitivity to context". This "contextualization" must embrace not only process of knowledge production but content of logical knowledge and university logical education partially. Proper attention to special material logics – varied addition to general logic – opens a new window of possibilities to science of logic. Orientation to social "robustness of knowledge" will make better both educational condition of discipline of logic and status of whole logic in up-todate society.